Vassiliki Theodorou and Despina Karakatsani, Strengthening Young Bodies, Building the Nation: A Social History of Child Health and Welfare in Greece (1890–1940) - Gardikas, Katerina (The Historical Review/La Revue Historique, 2021)
Review of: Vassiliki Theodorou and Despina Karakatsani, Strengthening Young Bodies, Building the Nation: A Social History of Child Health and Welfare in Greece (1890–1940)